Size-Induced Depression of First-Order Transition Lines and Entropy Jump in Extremely Layered Nanocrystalline Vortex Matter - Dolz, M.I.; Fasano, Y.; Cejas Bolecek, N. R. C.; Pastoriza, H.; Mosser, V.; Li, M.; Konczykowski, M.; Fasano, Yanina (American Physical Society, 2015)
Fil: Fasano, Y. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina; Universidad Nacional de Cuyo; Argentina